Mobility in daily life - The car and use of information and communication technology for family logistics - Randi J. Hjorthol (European Regional Science Association (ERSA), 2005)
The development of "new” family structures, with an increasing portions of divorced parents choose joint custody of the children, and a differentiation and distribution of daily activities has opened the way for new and more flexible forms for information and communication technology (ICT) to coordinate the interaction between family members. The need for flexible transport to link together activities is also an issue. The point of departure for this paper is to examine the interaction between the uses of ICT, in particular mobile phones, physical mobility and social life in an increasingly differentiated and distributed daily life among families with children. The questions addressed are how different families use ICT to coordinate and maintain relationships in everyday life and how ICT and physical mobility interact within this context. The empirical analysis is based on in-depth interviews of 25 families in the Oslo region. The analysis of the interaction between the car and the mobile phone indicate that the one will not replace the other. It is rather such that they represent technologies that complement each other and can perhaps mutually increase use. While the car is an extension of the body and which increases the physical range of the individual, the mobile telephone increases one's range of overview. To some degree the mobile telephone directs automobile use, in the sense that it may generate more trips since use of the mobile telephone means that there is not the need to plan daily activities. More of the activities are carried out spontaneously and daily life is more ad hoc, which also indicate more car uses. In the families of this study different time use arrangements are tied to the use of the car and the mobile telephone. At the one extreme we find the structured where all the activities are planned – both in time and space – and all the assignments are divided between the various members of the family. On the other hand we see families where everything is done spontaneously and there is very little planning aside from the fixed portions of life. The structured and ad hoc systems are two extremes on a scale where there are many alternative solutions. The families in this study represent positions between the extremes tending towards the ad hoc end of the spectrum. The car and the mobile telephone are devices that allow this type of organization, which seems to increase daily transport by car.
Keywords: 330